Cost-effectiveness analysis of sintilimab additional to chemoradiotherapy in high-risk locoregionally advanced nasopharyngeal carcinoma - She, Longjiang; Tang, Siqi; Han, Jiaqi; Liu, Guichao; Chen, Lusi; Zhang, Yang; Luo, Weijun; Zuo, Weihan; Ma, Feng; Xiong, Yan; Zhang, Ning (Frontiers in Pharmacology, 2025)
ObjectivesThe recently released CONTINUUM trial was the first phase 3 randomized study to demonstrate the efficacy and safety of immunotherapy in high-risk locoregionally advanced nasopharyngeal carcinoma (NPC), showing that sintilimab can bring clinical benefits to these populations.Materials and MethodsWe developed a Markov model to assess the cost and effectiveness of sintilimab plus standard therapy versus standard therapy alone. The primary outcomes included total costs, life-years, quality adjusted life years (QALYs) and incremental cost-effective ratios (ICERs). A series of sensitivity analyses were conducted to test the stability of the model.ResultsWhen compared to standard therapy, the addition of sintilimab yielded extra 3.10 QALYs at an increased cost of $24208.60, resulting in an ICER of $7819.669 per QALY. Our one-way sensitivity analysis indicated that the utility of event-free survival and the risk of leukopenia/neutropenia in immunotherapy group were the most influential factors impacting the results. The incorporation of sintilimab alongside standard therapy demonstrated a 95.4% probability of being cost-effective.ConclusionFirst-line induction-concurrent chemoradiotherapy with sintilimab was identified as a cost-effectiveness treatment option for high-risk locoregionally advanced NPC.